Students' Perceptions and Stress Levels Following Online Learning - Santika, Ririn Dewi; Wardiyah Daulay (Caring: Indonesian Journal of Nursing Science, 2021)
The spread of the COVID-19 disease has made the government issue an online learning process policy to break the virus spread chain. Online learning is a new learning method, and students are not used to it. They are struggling to the learning concept and do not understand how to use the supporting applications of online learning. If the students keep feeling anxious and distressed, they will be stressed out. This study was conducted to determine students' perception of online learning and their stress level during the COVID-19 pandemic at Senior Highschool 3 Sibolga (SMA Negeri 3 Sibolga). This study used a descriptive quantitative research design and univariate analysis. Samples were obtained using the Probability Sampling method, which is Simple Random Sampling. By using the method, 86 respondents were obtained. The instrument research is questionnaires on the perception of online learning. The results showed that 51 students (59.3%) perceived online learning negatively. In contrast, 35 students (40.7%) perceived online learning positively. In terms of stress level, 75 students (87.2%) have moderate stress, 3 students (3.5%) have mild stress, and 8 students (9.3%) have heavy stress. The study results recommend that community health centers education and guidance to the students on dealing with stress during online learning at school.